Web-Based Qr-Code System In The Library Data Processing Process At State Senior High School 1 Bangkinang City - Khairyzal Khairyzal; Cahyo Prianto (Universitas Islam Kuantan Singingi, 2026)
The school library plays an important role in supporting the learning process. However, the library data processing at SMA Negeri 1 Bangkinang Kota is still conducted manually, which may lead to problems such as data recording errors, slow services, and difficulties in generating reports. Therefore, an information system is needed to improve the effectiveness and efficiency of library data management. This study aims to design and develop a Web-Based Library Information System integrated with QR-Code technology. The system is designed to manage book data, member data, borrowing and returning transactions, and automated report generation. The system development method used in this study is the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The result of this study is a web-based library application that is able to accelerate transaction processes through the use of QR-Code technology, reduce data input errors, and facilitate librarians in managing and generating library reports. Based on the results of testing using the Black Box Testing method, the developed system operates according to functional requirements and can be implemented as a solution to improve the quality of library services at SMA Negeri 1 Bangkinang Kota.